Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

Leading in disadvantaged Zimbabwean school contexts: Female school heads’ experiences of emotional labour - Zikhali, Joyce; Perumal, Juliet (Educational Management Administration and Leadership, 2016)
This qualitative multiple case study explored the sources of emotional stress experienced by 12 female Zimbabwean primary heads leading in socio-economic disadvantaged schools in Masvingo District and their attempts to alleviate the challenges that the children from these disadvantaged contexts presented them with. Data was generated through individual semi-structured interviews, and observations and the data was analysed thematically to elicit the sources of their emotional labour that emanated from stress-related cultural and contextual factors. The study revealed that despite the school heads experiencing anxiety, pain, sorrow, sympathy, frustration, sadness, and concern they were happy about their appointments to leadership positions. The sources of their emotional stress were related to the plight of children; stereotypical gender expectations; lack of parental cooperation; and unrealistic professional and social expectations. The study suggests wellness recesses; the establishment of social networks through which heads could share their experiences; and professional development programmes on stress management as possible interventions that could help the heads deal with these stressful circumstances. © 2015, © The Author(s) 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; directrices d'école; enfants orphelins; environnement; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail émotionnel; zimbabwe; éducation

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis